Simultaneous radio-ulnar cannulation: shifting gears from ‘feasibility’ to ‘applicability’ - Ankit Kumar Sahu (SpringerOpen, 2021)
Abstract Conventionally, routes of vascular access commonly include femoral and radial arteries with brachial, ulnar and subclavian arteries being rarely used for coronary interventions. Non-femoral arterial access is being increasingly preferred to minimise groin puncture site complications, prolonged immobilization and duration of hospital stay. However, radial artery cannulation is also fraught with fears of tortuosity, loops, vascular spasm, perforation, pseudoaneurysm formation, arm hematoma and arterial occlusion. In contemporary practice when most of the coronary procedures are being done via transradial access, encountering one of the above-mentioned hurdles often forces the operator to switchover to femoral access. Here, we explore the rationale, feasibility, operational logistics, clinical implications and future directions for using simultaneous radio-ulnar arterial access in the same extremity.